2019
DOI: 10.3390/cancers11050595
|View full text |Cite
|
Sign up to set email alerts
|

Blastic Plasmacytoid Dendritic Cell Neoplasm: State of the Art and Prospects

Abstract: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is an extremely rare tumour, which usually affects elderly males and presents in the skin with frequent involvement of the bone-marrow, peripheral blood and lymph nodes. It has a dismal prognosis, with most patients dying within one year when treated by conventional chemotherapies. The diagnosis is challenging, since neoplastic cells can resemble lymphoblasts or small immunoblasts, and require the use of a large panel of antibodies, including those against C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 114 publications
0
83
0
7
Order By: Relevance
“…Regimens for AML/ALL like hyper-CVAD, methotrexate and cytarabine, lymphoma chemotherapies like CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone) and CHEOP (CHOP plus etoposide) may be effective 1 7 8 15 16. CNS prophylaxis using intrathecal therapy is highly recommended for BPDCN given the high risk of CNS involvement especially in relapses 1 7 8 15 16. Newer modalities include agents like venetoclax which is a BCL2 inhibitor effective in BPDCN 7 17.…”
Section: Discussionmentioning
confidence: 99%
“…Regimens for AML/ALL like hyper-CVAD, methotrexate and cytarabine, lymphoma chemotherapies like CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone) and CHEOP (CHOP plus etoposide) may be effective 1 7 8 15 16. CNS prophylaxis using intrathecal therapy is highly recommended for BPDCN given the high risk of CNS involvement especially in relapses 1 7 8 15 16. Newer modalities include agents like venetoclax which is a BCL2 inhibitor effective in BPDCN 7 17.…”
Section: Discussionmentioning
confidence: 99%
“…Multiagent chemotherapy regimens as in ALL are the most accepted applications for these patients. The disease often relapses after chemotherapy and becomes resistant to the previous drugs [3,4,11,13,23,25].…”
Section: Antibodymentioning
confidence: 99%
“…The tumor cells typically express CD4, CD56, CD43, CD45RA, and plasmacytoid dendritic cell antigens (CD123, CD303, TCL1A, CD2AP, SPIB, and type 1 interferon-dependent molecule MX1) [3]. The molecular profile showed that this entity is much more related to myeloid neoplasms [4].…”
Section: Introductionmentioning
confidence: 99%
“…Blastic plasmacytoid dendritic cell neoplasm (BPDCN) represents the malignancy with the most promising clinical applications of CD123 targeted therapy. BPDCN is an extremely rare clonal hematological malignancy of plasmacytoid dendritic cell precursors, usually affecting elderly males and presenting in the skin with frequent involvement of the bone marrow, peripheral blood and lymph nodes [73,74]. The epidemiology, pathology, molecular abnormalities and clinical features of BPDCN were recently reviewed [73,74].…”
Section: Introductionmentioning
confidence: 99%